2002
DOI: 10.1111/j.1654-109x.2002.tb00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of species‐rich flood‐plain meadows from abandoned arable fields in NE France

Abstract: Attempts to restore species-rich flood-plain meadows from abandoned arable fields in the valley of the river Meuse, NE France, were studied. The study area was sown with a commercial seed mixture, composed of Phleum pratense, Festuca pratensis, Lolium perenne and Trifolium repens. The above-ground vegetation in the study area 1, 2 and 3 yr after restoration was compared to (1) the vegetation present during the previous 5-yr fallow stage and (2) target flood-plain meadows. Before restoration, the above-ground f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…For example, both Stevenson et al (1995) and Lawson et al (2004) reported very poor establishment of the sown species. The establishment of sown species is often delayed until after year 1 following restoration (Vécrin et al 2002). In other cases, establishment was highly successful even in year 1 (Manchester et al 1999).…”
Section: Restoration Success After Seed Sowing and Spontaneous Succesmentioning
confidence: 99%
“…For example, both Stevenson et al (1995) and Lawson et al (2004) reported very poor establishment of the sown species. The establishment of sown species is often delayed until after year 1 following restoration (Vécrin et al 2002). In other cases, establishment was highly successful even in year 1 (Manchester et al 1999).…”
Section: Restoration Success After Seed Sowing and Spontaneous Succesmentioning
confidence: 99%
“…However, the hydrological, geomorphological and biological heterogeneity and variability of river-floodplain systems, both temporally and spatially, can complicate the restoration schemes (Amoros et al, 1987). The role of gradients in hydrological and soil nutrient conditions, determined by the flood regime, together with aspects of ARTICLE IN PRESS spatial and temporal disturbance and connectivity patterns in the river system was already documented for the floodplain grassland biodiversity conservation of the River Meuse (Geilen et al, 2004;Grevilliot et al, 1999;Grevilliot & Muller, 2002;Van Looy et al, 2006;Vécrin et al, 2002). Although the river corridor plants benefit from floods, flooding also bears the risk of local destruction of habitat and populations.…”
Section: Implications For Conservation and Restoration: The Conservatmentioning
confidence: 96%
“…Generally, the species composition and degree of coverage of recovered vegetation profoundly affect wetland ecosystem functions and habitat quality of the animals. Furthermore, Ó International Consortium of Landscape and Ecological Engineering and Springer-Verlag Tokyo 2006 initial species composition of the restored vegetation can fundamentally affect the site vegetation for a long time (Vé crin et al 2002;Bissel et al 2004). Therefore, the revegetation methodology, i.e., how and what species should be introduced to the site, is an important factor in achieving ecologically sound wetland restoration.…”
Section: Introductionmentioning
confidence: 98%
“…Nowadays, restoration projects of a wide variety of wetland types have been implemented or planned, including floodplain wetlands converted for agricultural use (Vé crin et al 2002;Middleton 2003), abandoned peatlands (Rochefort et al 2003;Cobbaert et al 2004), and hydrologically altered wet meadows (Galatowitsch and van der Valk 1996;Smith et al 2002;Nakamura et al 2003). The restoration or rehabilitation of wetlands around rivers and lakes has also been growing rapidly since the early 1990s in Japan (Nakamura et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation